Paradigm for the development of a Lanna music curriculum in higher education in Northern Thailand - Pitupumnak, Khanithep (Universiti Pendidikan Sultan Idris, 2018)
Paradigm for the development of a Lanna music curriculum in higher education in Northern Thailand by Pitupumnak, Khanithep